2019
DOI: 10.1136/bmjopen-2018-027450
|View full text |Cite
|
Sign up to set email alerts
|

Association between early-life exposure to the Great Chinese Famine and poor physical function later in life: a cross-sectional study

Abstract: ObjectivesThis study aimed to evaluate the association between early-life exposure to the Great Chinese Famine (1959–1961) and the prevalence of poor physical function in midlife.DesignA population-based historical prospective study was performed as part of a wider cross-sectional survey. Exposure to famine was defined by birthdate, and participants were divided into non-exposed group, fetal-exposed group and infant-exposed group.Setting and participantsA total of 3595 subjects were enrolled into the study fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“… 14 A recent study showed that men exposed to the Great Chinese Famine presented considerably decreased physical function in their later life, but the association was only seen in the fetal exposed group. 15 This discrepancy could be explained by the fact that we used a composite score involving muscle strength and physical performance to assess sarcopenia, whereas the two previous studies used a single indicator. Scores derived from a single test are likely to be more unilateral than scores derived from composite tests.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 14 A recent study showed that men exposed to the Great Chinese Famine presented considerably decreased physical function in their later life, but the association was only seen in the fetal exposed group. 15 This discrepancy could be explained by the fact that we used a composite score involving muscle strength and physical performance to assess sarcopenia, whereas the two previous studies used a single indicator. Scores derived from a single test are likely to be more unilateral than scores derived from composite tests.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study showed that men who were exposed to the Great Chinese Famine during their fetal stage presented considerably decreased physical function in their later life, but the association was not observed in the other exposed groups. 15 However, the indicator in the previous publication was physical function, which although related to the status of muscle and bone, does not allow diagnosis even for PS. Thus, the question of whether malnutrition exposure during stages of early life would lead to the risk of sarcopenia in older age still remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…The childhood socioeconomic status questionnaire was prone to recall bias, which may potentially lead to underestimation of the association between variables. However, the questionnaire has been widely used in previous research (33,(66)(67)(68). Another limitation was that the food consumption score did not represent all food insecurity proxies.…”
Section: Discussionmentioning
confidence: 99%
“…The present paper shows that older people from two different countries, and particularly Brazilians, often rated their own health as “very good” or “good.” There are important differences between Brazil and Portugal, both in the prevalence of positive perceptions of one's own health and in its impact on mental and physical health. Results from comparisons between countries suggest a need for investing in improving one's health throughout life, because childhood living conditions can be considered distal determinants of independent performance of activities of daily living and of reduced burden of chronic diseases among older adults ( 111 , 112 ). Personality, expressed through the trait neuroticism, deserves special attention.…”
Section: Discussionmentioning
confidence: 99%